A cybernetic model of corporate responsibility - sensing changes in business and society. (2012) - Roome, Nigel
Corporate responsibility (CR), as a business contribution to sustainable development, implies that the environment affects the organisation and the organisation reacts to its changing environment. In this way, CR can be understood as a cybernetic system operating across the interface between the organisation and its environment. This paper elaborates a cybernetic model of CR, and uses it to distinguish ways that managers sense change in their environment. Three ways to 'sense' change are compared: following trends, issues and events; picking up signals from stakeholders; and adjusting to sustainable development as a specific definition of 'progress'. The paper discusses the merits and limits of each approach. Conclusions are drawn in terms of implications for managing CR. Moreover, the cybernetic model is held to provide for a theory of CR that is more in line with the multi-disciplinary nature of practice than is found in ideas that derive from business ethics or stakeholder theory.